Governance analysis for urban wholesale to household’s food waste prevention and reduction in Sri Lanka - Aheeyar, Mohamed M. M.; Jayathilake, Nilanthi; Bucatariu, C.; Reitemeier, Maren; Bandara, Ayomi; Thiel, Felix; Drechsel, Pay (FAO; International Water Management Institute, 2023)
This report explores and analyses the governance framework (i.e. policies, laws, and regulations) relevant to urban food waste (FW) prevention and reduction in the wholesale, retail, hospitality (restaurants, hotels), food services (schools, hospitals), and households in Sri Lanka. The project "Innovative approaches to reduce, recycle and reuse food waste in urban Sri Lanka" was implemented from June 2019 to August 2021 under the oversight of the Ministry of Urban Development and Housing and in collaboration with the Food and Agriculture Organization of the United Nations (FAO) and the International Water Management Institute (IWMI).